(3YhGQa GdeYGQas - (3TgGH GdOjf CHh GdeLjH YHO GdbGgQ Hf YHO Gddg Hf eMeO GdSgQhQOjs ((3CMeO Hf eMeO Hf UZjQ GdhaGFi GdeOfi GdMQjQi GdUhai s)
(3ChdgG (B:s
(3jHOC HGdHGH GdKGdK hGdKdGKhf ai COH GdWgGQI hebOeGJgG s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3Ef Gddg SHMGfg EPG CMH YHOkG fGOi LHQjd ai GdSeGA hjhVY dg GdbHhd ai GdCQV hGdMeO ddg QH GdYGdejf Je cJGH YhGQa GdeYGQa s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1177s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs